Alternatywy wobec jednowymiarowości. Fenomen polskiej kultury niezależnej w PRL - Dabert, Dobrochna (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
In this article devoted to the independent culture in Polish People’s Republic, I put into dichotomic doubt the concept based on the clear division between the official and independent culture. The forms of creative activity that escaped the state censorship between 1976 and 1989 radically disrespected the directives of the state’s cultural policy, yet many years before the emergence of ‘the second circulation’, there were already numerous initiatives that sparked a rich spectrum of independent activity. The authors’ strategies to remain independent changed over time, to varying extent distanced the authors from the official artistic life and differed depending on the character of the authors’ intellectual activity. In the article, I attempt to prove the relatively weak influence of the ‘official dependent culture’ that fully respected the authorities’ instructions, and I propose a classification of creative strategies that also emerged in the official culture and allowed for a relatively free development of art and science. Using multiple examples from literature, cinema, visual arts, music and science, I discuss ‘controlled culture escaping the ideological instructions’, ‘official niche culture’, ‘culture confronting the limitations’, ‘licensed Catholic culture’, ‘second circulation culture’ and ‘third circulation culture.’ The practice of searching for a way out of the official one-dimensionality allowed Polish cultural identity to continue and save its most valuable intellectual and artistic values.